OR09-4SCRIPT IN A DAY (SCID) INTERVENTION FOR INDIVIDUALS WHO ARE INJECTING OPIATES: RESULTS FROM A MIXED METHODS FEASIBILITY RANDOMISED CONTROL TRIAL. (September 2014) - Beattie, A. M.; Barber, M.; Marques, E.; Greenwood, R.; Ingram, J.; Ayres, R.; Neale, J.; Rees, A.; Coleman, B.; Hickman, M.
Abstract : Background. Opiate substitution treatment (OST) reduces the harm of injecting and opiate dependence. The SCID trial tested whether offering people who inject heroin attending a low threshold agency immediate access to OST via specialist primary care increased the number in OST at 3 months, compared to offering advice and case management. Methods. Un-blinded randomised control trial with a qualitative study was conducted at Bristol Drugs Project needle exchange. A total 311/1371 individuals were eligible and 100 consented. Twenty were interviewed. Findings. Follow-up was 86%. At 3 months 51% & 47% of the intervention and control group were in OST. Opiate use reduced by 79% and 72% respectively. Physical and mental health improved but there was insufficient evidence of differences between groups. Motivation to participate concerned the need to secure treatment. Securing OST included improvements in health, self-care, harm reduction and crime. Conclusions. Trial conduct was successful but there was insufficient evidence of an effect compared to case management. Participating in the trial enabled intervention participants to obtain treatment for their drug use. Completing baseline questionnaires seemed to be a motivating factor for the control to seek OST from their GP. Further development and evaluation of case management approaches is warranted.